2021
DOI: 10.1002/ece3.7385
|View full text |Cite
|
Sign up to set email alerts
|

Developing a flexible learning activity on biodiversity and spatial scale concepts using open‐access vegetation datasets from the National Ecological Observatory Network

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Here, we demonstrate how hands-on activities embedded into ready-to-use teaching modules can be used to successfully teach students ecological concepts that span multiple temporal and spatial scales. Similar to this study, Styers et al (2021) observed gains in students' understanding of cross-scale biodiversity processes following the use of hands-on teaching modules that analyzed NEON data collected across multiple spatial scales [28]. Taken together, our study and Styers et al (2021) highlight the utility of hands-on activities that analyze real environmental data to teach students complex concepts spanning multiple scales, an important component of macrosystems ecology [28].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Here, we demonstrate how hands-on activities embedded into ready-to-use teaching modules can be used to successfully teach students ecological concepts that span multiple temporal and spatial scales. Similar to this study, Styers et al (2021) observed gains in students' understanding of cross-scale biodiversity processes following the use of hands-on teaching modules that analyzed NEON data collected across multiple spatial scales [28]. Taken together, our study and Styers et al (2021) highlight the utility of hands-on activities that analyze real environmental data to teach students complex concepts spanning multiple scales, an important component of macrosystems ecology [28].…”
Section: Discussionsupporting
confidence: 76%
“…Multiple recent studies have highlighted the challenges of teaching concepts and processes that span multiple spatial and/or temporal scales in undergraduate science courses [26,28], a key component of the sub-discipline of macrosystems ecology. Here, we demonstrate how hands-on activities embedded into ready-to-use teaching modules can be used to successfully teach students ecological concepts that span multiple temporal and spatial scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental network data have also inspired educational material for academic year undergraduate classes (Gram & Jones, 2018; Langen et al, 2014). The NEON Learning Hub provides access to teaching modules and tutorials, some of which are designed by faculty from primarily undergraduate institutions, for introducing undergraduates to data science, spatial scaling, and macrosystems biology concepts (e.g., Styers et al, 2021). Other course modules such as those from Project EDDIE (Environmental Data‐Driven Inquiry and Exploration; O'Reilly et al, 2017) provide instructor and student materials on a number of macrosystems ecology topics.…”
Section: Linking Networkmentioning
confidence: 99%